Pengembangan Potensi Desa Wisata Melalui 3A Dan Penerapan CHSE Di Desa Cihanjawar, Kabupaten Purwakarta Dalam Masa Adaptasi Kebiasaan Baru - ER. Ummi Kalsum; Djauhar Arifin; Marsianus Raga; Daeng Noerdjamal; Bambang Sapto Utomo (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2021)
The Covid-19 pandemic has had a broad impact on the global tourism world since the end of 2019. Data shows that international tourist arrivals declined sharply in the first half of 2020 (-65%) compared to 2019. The strategy has been implemented by various special countries, the Indonesian Ministry of Tourism proclaimed the principle of Adapting to New Habits (AKB) in the Indonesian tourism industry as an integral part of the permit to reopen tourism businesses and destinations. The IMR principles in Indonesian tourism are applied from a strategic and technical perspective as well as from supply chain changes to the needs and demands of the management of tourists. This research was produced to be able to see the readiness of tourist destinations in the region, especially Tourism Villages in dealing with the Covid-19 situation and conditions with several strategies that have been set by the central government starting from CHSE and digitalization for Tourism Villages. This study used a quantitative research method with a description that describes each goal starting from the 3A condition, the Health Protocol, and its digitization. This mapping is very important to determine the direction of the potential development of Cihanjawar Tourism Village as a tourist destination